Mycorrhizal fungi inoculation and phosphorus fertilizer on growth, essential oil production and nutrient uptake in peppermint (Mentha piperita L.) - Arango, María Cecilia (2012)
This study evaluated the effects of inoculation with the arbuscular mycorrhizal fungi Glomus mosseae, Glomus intraradices A4 and Glomus intraradices B1 and two phosphorus levels (10 and 40 mg kg-1) on root colonization, plant growth, nutrient uptake and essential oil content in Mentha piperita L. The experiment was carried out in a greenhouse, in 4x2 factorial arrangement, in completely randomized design. At sixty days after transplanting, the mycorrhizal plants had significantly higher fresh matter, dry matter and leaf area compared to non-mycorrhizal plants. The inoculation increased P, K and Ca levels in the shoot which were higher under 40 mg P kg-1 of soil. Plants grown with 40 mg P kg-1 soil increased the essential oil yield per plant by about 40- 50% compared to those cultivated with 10 mg P kg-1, regardless of the mycorrhizal treatment. Among the studied fungal species, inoculation with G. intraradices A4 and a high level of P significantly increased plant growth and essential oil yield, compared to the other studied mycorrhizal fungal species. In conclusion, inoculation of arbuscular mycorrhizal fungi into peppermint plants is a feasible alternative to increase the essential oil production and reduce the use of fertilizers required to obtain economic production of peppermint under phosphorus-deficient soil condition.